Effects of Topical Emu Oil on Burn Wounds in the Skin of Balb/c Mice - Mohammad Afshar; Reza Ghaderi; Mahmoud Zardast; Parvin Delshad (Dermatology Research and Practice)
The goal of this study was to determine the effect of topical Emu oil on the healing of burn wounds and hair follicle restoration in superficial II-degree burns in the skin of Balb/c mice. Thirty-two male Balb/c mice with burns on the back of the neck were divided into two groups: The Emu oil group received topical Emu oil twice daily, whereas the control was left untreated. Skin biopsies were obtained on days 4, 7, 10, and 14 of the experiment. Then the specimens were viewed with Olympus SZX research microscope. The Emu oil treated burns were found to heal more slowly and inflammation lasted longer in this group. The number of hair follicles in the margins of the wounds increased through time in the Emu oil group compared to the control group. Also, the hair follicles in the Emu oil group were in several layers and seemed to be more active and mature. Moreover, Emu oil had a positive effect on fibrogenesis and synthesis of collagen. The findings indicate that although Emu oil delays the healing process, it has a positive effect on wound healing and it increases the number of hair follicles in the margins of the wound.